Endocrine disruptor chemicals exposure and female fertility declining: from pathophysiology to epigenetic risks - Tricotteaux-Zarqaoui, Sophian; Lahimer, Marwa; Abou Diwan, Maria; Corona, Aurélie; Candela, Pietra; Cabry, Rosalie; Bach, Véronique; Khorsi-Cauet, Hafida; Benkhalifa, Moncef (Frontiers in Public Health, 2024)
Over the last decades, human infertility has become a major concern in public health, with severe societal and health consequences. Growing evidence shows that endocrine disruptors chemicals (EDCs) have been considered as risk factors of infertility. Their presence in our everyday life has become ubiquitous because of their universal use in food and beverage containers, personal care products, cosmetics, phytosanitary products. Exposure to these products has an impact on human reproductive health. Recent studies suggest that women are more exposed to EDCs than men due to higher chemical products use. The aim of this review is to understand the possible link between reproductive disorders and EDCs such as phthalates, bisphenol, dioxins, and pesticides. In women, the loss of endocrine balance leads to altered oocyte maturation, competency, anovulation and uterine disorders, endometriosis, premature ovarian insufficiency (POI) or embryonic defect and decreases the in vitro fertilization outcomes. In this review, we consider EDCs effects on the women’s reproductive system, embryogenesis, with a focus on associated reproductive pathologies.